Control of effective factors in lost and damage ratio of constructionmaterials - nan, nan; nan, nan; nan, nan (Iraqi Journal of Civil Engineering, 2008)
Construction materials are very important in industrial construction. The factors which affect the lost and damage ratio on were studied by classification the lost and damage in the materials. In addition the following factors : 1-Estimation and design. 2-Storege and delivery. 3-Effisincy of management. 4-Applied guard and security on materials storage. 5-Approsh of material transport. Were also studied determination of the effect ratio for every factors was tabulated in order to use by the management for control the lost and damage. Simple equations were presented to help the constructional management to find the modified ratio of lost in according to the effect factors. It was found some conclusion and recommendation which can direct the construction managements to use the suggested tables and equations to reduce the damage ratio of construction materials.